S53 Outcomes of the RePneu Endobronchial Coils For the Treatment of Severe Emphysema with HyperinflaTion (RESET) Trial. (19th November 2012) - Zoumot, Z; Kemp, S; Chaudhuri, R; Caneja, C; Bicknell, S; Hopkinson, N; Singh, S; Ross, E; Shah, P
Abstract : Background: The predominant pathophysiology in severe emphysema with gas trapping and hyperinflation is that of dynamic airway collapse on minimal expiratory effort. This limits the benefit from drug therapy. Safer and cheaper alternatives to lung volume reduction surgery (LVRS), which has success in selected patients with low exercise capacity and upper lobe-predominant emphysema, are being developed. Endobronchial valve treatment has been shown to be beneficial to patients with heterogenous disease in the absence of collateral ventilation. RePneu Lung Volume Reduction Coils (LVRCs) are self-actuating implantable devices composed of nitinol. They are implanted bronchoscopically using conscious sedation. The LVRC is delivered into targeted airways using fluoroscopic guidance, and when its sheath is removed recoils to it original pre-determined shape. Methods: In a prospective randomised study of LVRCs on patients with severe emphysema and hyperinflation, 63 patients were screened at 3 centres in the United Kingdom with 23 randomised to treatment with LVRCs and 24 to best medical care (control). LVRC patients were initially treated in one lung, with the contralateral lung treated after one month if appropriate. The primary end point was the difference between treatment and control groups in the St. George's Respiratory Questionnaire (SGRQ) 90 days post-final treatment. The trial is registered with ClinicalTrials.gov (NCT01334307 ). Results: Significant improvements in the treatment group compared to control group were observed for the primary end point mean SGRQ (Δ-10.54 points, p=0.004), as well as secondary end points mean six-minute walk distance (Δ+70.39 metres, p<0.001) and forced expiratory volume in one second (Δ+12.81%, p=0.009). Between group difference in change in mean residual volume did not reach significance (Δ-0.35 litres, p=0.051), despite a 0.64 litre reduction in the treatment group. There was a good safety profile with treatment. Conclusions: Treatment with endobronchial coils in patients with severe emphysema and hyperinflation significantly improves quality of life, exercise capacity and pulmonary function with a good safety profile. LVRCs present a novel, safe, and minimally invasive treatment option for patients with both homogenous and heterogenous emphysema, with benefits unaffected by collateral ventilation. A larger randomised controlled pivotal trial with longer follow-up is now needed. Funding shared by PneumRx and study sites.